Comparison of Oral Contrast‐Enhanced Transabdominal Ultrasound Imaging With Transverse Contrast‐Enhanced Computed Tomography in Preoperative Tumor Staging of Advanced Gastric Carcinoma. (24th June 2017) - He, Xuemei; Sun, Jing; Huang, Xiaoling; Zeng, Chun; Ge, Yinggang; Zhang, Jun; Wu, Jingxian
Abstract : Objectives: This study assessed the diagnostic performance of transabdominal oral contrast‐enhanced ultrasound (US) imaging for preoperative tumor staging of advanced gastric carcinoma by comparing it with transverse contrast‐enhanced computed tomography (CT). Methods: This retrospective study included 42 patients with advanced gastric cancer who underwent laparoscopy, radical surgery, or palliative surgery because of serious complications and had a body mass index of less than 25 kg/m 2 . A cereal‐based oral contrast agent was used for transabdominal oral contrast‐enhanced US. Retrospective analyses were conducted using preoperative tumor staging data acquired by either transabdominal oral contrast‐enhanced US or transverse contrast‐enhanced CT. Both contrast‐enhanced US and contrast‐enhanced CT examinations were reviewed by 2 experienced radiologists independently for preoperative tumor staging according to the seventh edition of the TNM classification. The accuracy, sensitivity, and specificity were calculated by comparing the results of contrast‐enhanced US and contrast‐enhanced CT with pathologic findings. The overall accuracies of the imaging modalities were compared by the McNemar test. Results: No significant difference was noted in the overall accuracy of transabdominal oral contrast‐enhanced US (86% [36 of 42]) and transverse contrast‐enhanced CT (83% [35 of 42] P > .999). For stage T2 to T4 gastric cancer, the accuracies of transabdominal oral contrast‐enhanced US were 88%, 86%, and 98%, respectively, and those of transverse contrast‐enhanced CT were 93%, 83%, and 90%. Conclusions: The overall accuracy of transabdominal oral contrast‐enhanced US was comparable with that of transverse contrast‐enhanced CT for preoperative tumor staging of advanced gastric cancer.